Structural and Thermal Unusual Properties in Invar Behavior of Ni-Mn Alloys (Baghdad Science Journal, 2020)
The Invar effect in 3D transition metal such as Ni and Mn, were prepared on a series composition of binary Ni1-xMnx system with x=0.3, 0.5, 0.8 by using powder metallurgy technique. In this work, the characterization of structural and thermal properties have been investigated experimentally by X-ray diffraction, thermal expansion coefficient and vibrating sample magnetometer (VSM) techniques. The results show that anonymously negative thermal expansion coefficient are changeable in the structure. The results were explained due to the instability relation between magnetic spins with lattice distortion on some of ferromagnetic metals.